Blue-phase templated fabrication of three-dimensional nanostructures for photonic applications. - Castles, F; Day, F; Morris, S; Ko, D; Gardiner, D; Qasim, M; Nosheen, S; Hands, P; Choi, S; Friend, R; Coles, H (2012)
A promising approach to the fabrication of materials with nanoscale features is the transfer of liquid-crystalline structure to polymers. However, this has not been achieved in systems with full three-dimensional periodicity. Here we demonstrate the fabrication of self-assembled three-dimensional nanostructures by polymer templating blue phase I, a chiral liquid crystal with cubic symmetry. Blue phase I was photopolymerized and the remaining liquid crystal removed to create a porous free-standing cast, which retains the chiral three-dimensional structure of the blue phase, yet contains no chiral additive molecules. The cast may in turn be used as a hard template for the fabrication of new materials. By refilling the cast with an achiral nematic liquid crystal, we created templated blue phases that have unprecedented thermal stability in the range -125 to 125 °C, and that act as both mirrorless lasers and switchable electro-optic devices. Blue-phase templated materials will facilitate advances in device architectures for photonics applications in particular.